Conformational analysis of acetamide in the ground and lowest excited electronic states. (May 2017) - Tukachev, N.V.; Bataev, V.А.; Godunov, I.А.
Abstract: For acetamide molecule (CH3 CONH2 ) in the ground (S0 ) and lowest excited singlet (S1 ) and triplet (T1 ) electronic states calculations of equilibrium geometry parameters, harmonic vibrational frequencies and barriers to conformational transitions (also conformer energy differences in excited states) using following ab initio methods: MP2, CCSD(T), CASSCF, CASPT2 and MRCI were performed. One-, two- and three-dimensional potential energy surface (PES) sections by different large amplitude motions (LAM) coordinates were calculated by means of MP2/aug-cc-pVTZ (S0 ) and CASPT2/cc-pVTZ (S1, T1 ). As a result of electronic excitation, both CCON and CNH2 fragments become pyramidal. On 2D PES sections by torsion (CN) and inversion coordinates there are six minima forming three pairs of enantiomers. Using PES sections different anharmonic vibrational problems were solved and the frequencies of large amplitude vibrations were estimated. Graphical abstract: Highlights: For acetamide in S1 and T1 states, three pairs of equivalent conformers were found. Using corresponding 2D PES section, frequencies of NH2 out-of-plane and CN torsion vibrations were computed with good agreement with experiment for acetamide in S0 electronic state. Harmonic and 1D approximations are inconsistent in evaluating frequencies of out-of-plane vibrations and inversions in this molecule. Acetamide in S1 state has much in common with T1 .